Hadith Matruk (Studi Kajian Hadith) - Saifuddin Syuhri (Asy-Syari’ah : Jurnal Hukum Islam, 2020)
The hadith can be used as hujjah if it is known that the hadith has been declared shoheh by some hadith scholars. Or at least is included hasan hadith. While the hadith can not be used as evidence to determine a law.The criteria of the hadith shoheh, hasan, and dloif are clearly explained in several books compiled by scholars of ‘hadith in the second to third centuries of Hijriyah. However, at present it is necessary to re-codify the science of hadith, as a lecture material for a comprehensive understanding of the position of the hadith in the level of Islamic law that is second only to the Qur’an.